Dengue: clinical forms and risk groups in a high incidence city in the southeastern region of Brazil - Ivana Macedo Cardoso; Aline de Souza Areias Cabidelle; Patrícia de Castro e Leão Borges; Carolina Ferreira Lang; Fabrício Greco Calenti; Larissa de Oliveira Nogueira; Aloisio Falqueto; Crispim Cerutti Junior (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: The article describes the epidemiologic profile of dengue cases in Vitória, the capital of Espírito Santo, Brazil, from 2000 to 2009, aimed at identifying risk groups regarding the incidence and severity of the disease. METHODS: Confirmed cases of dengue among city residents during ten years were classified as dengue fever, dengue hemorrhagic fever, dengue shock syndrome and dengue with complications, and analyzed according to sex, age, race-color and education. RESULTS: The proportion of dengue cases was highest among women aged 20 to 29 years-old and similar between whites and blacks. A gradual decrease occurred in the percentage of dengue cases in the population aged 15 years-old or more, in the historical series of 10 years, and a growing increase in individuals less than 15 years-old, showing statistical significance. The fatality rate ranged from zero to 0.3% for all forms of dengue and from 0.2% to 18.2% for severe forms. CONCLUSIONS: The profile of those affected by the disease in the municipality is similar to those affected in Brazil. The increasing number of cases in individuals under 15 years-old corroborates the results of recent studies in other Brazilian municipalities.